Pemikiran Pembaharuan Muḥammad `Abd Allāh Dirāz terhadap Universiti al-Azhar: Muḥammad `Abd Allāh Dirāz’ Reformation Ideas on University of al-Azhar - Ali, Muhammad Hanif; Mohd Yusoff, Mohd Yakub @ Zulkifli; Jamil, Asyraf Isyraqi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
The article explores the efforts taken to restore and renew the glory of al-Azhar University; a millennium of an Islamic educational institution. The discourse attempts to highlight reformation ideas that have been triggered by one of al-Azhar’s scholars, Muḥammad ‘Abd Allāh Dirāz (1894-1958 AD.). This is based on the review of several sources related to al-Azhar’s reformation history, where Dirāz seemed to have no role in the efforts. However, based on some of his writings, it can be concluded that he has the ideas of reformation which are worthy to be emphasized and developed. The discussion were carried out through analysis on several articles and copies of correspondence between Dirāz and the management of al-Azhar. The study found that his ideas can be divided into four aspects, namely the foundation of education, the method of educational implementation, the method of assessment and monitoring, as well as the internationalization of institution.